Sinergi Keputusan Investasi dan Validasi Syariah dalam Pengembangan Produk Pembiayaan UKM: Studi Kasus PT Syariah - Suci Rahmawati; Azmia Siti Munasifah; Wafa Syakila; Neng Nazma Aulia; Joni Ahmad Mughni (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study explores the synergy between investment decisions and sharia compliance validation in developing financial products for SMEs, with a case study of PT Syariah Sejahtera. The research emphasizes the importance of integrating halal principles into investment analysis using methods such as Payback Period (PBP), Net Present Value (NPV), and Internal Rate of Return (IRR). The validation process involves systematic steps, including initial identification, legal analysis, consultation with the Sharia Supervisory Board, and issuance of fatwas to ensure products comply with Islamic law. Results demonstrate that effective integration enhances product credibility, attracts market interest, and contributes to economic and social welfare, especially in the agricultural SME sector. The findings suggest that combining financial analysis with strict halal validation fosters sustainable growth of sharia-based financial services, reinforcing trust and regulatory compliance.